Deepfake sebagai Sarana Pemerasan dalam Perspektif Hukum Pidana Indonesia - Rio Irandha Putra; Wahab Aznul Hidaya; Sokhib Naim (Fakultas Hukum Universitas Mulawarman, 2026)
This research analyzes Indonesia's legal construction in addressing the misuse of deepfake technology in the criminal offense of extortion, examining both substantive criminal law and evidentiary aspects. The findings indicate that the extortion provision under Article 482 paragraph (1) of the National Penal Code is inadequate to address deepfake-based threats, as the element of